2022
DOI: 10.1142/s0219498823502584
|View full text |Cite
|
Sign up to set email alerts
|

Some differential identities on prime Banach algebras

Abstract: In this paper, we investigate the commutativity of a Banach algebra [Formula: see text] provided with a continuous derivation satisfying algebraic identities involving nonvoid open subsets of [Formula: see text] Furthermore, we provide examples to show that various restrictions in the hypothesis of our theorems are not superfluous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Numerous results in the literature concerning the commutativity of a prime and semi-prime Banach algebra are proved, for example, in 2022, M. Moumen, L. Taoufiq and L. Oukhtite [5] showed that if X is a prime Banach algebra having two non-void open subsets H 1 and H 2 such that for all (x, y)…”
Section: Introductionmentioning
confidence: 99%
“…Numerous results in the literature concerning the commutativity of a prime and semi-prime Banach algebra are proved, for example, in 2022, M. Moumen, L. Taoufiq and L. Oukhtite [5] showed that if X is a prime Banach algebra having two non-void open subsets H 1 and H 2 such that for all (x, y)…”
Section: Introductionmentioning
confidence: 99%